(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
In this article, the operator, creating with the help of a camera and lens, delivers to the viewer the idea of a screenwriter, artist, director and the physiological-mental state of the actor. If in a theatrical performance the live communication of the actors on the stage gives the viewer the effect of participation, then in a feature film this task is assigned to the images of the operator. As the sensitive lens of the kinocamera involuntarily copies the experience of the heroes into the soul of the viewer, a state of joint anguish arises from their grief, rejoicing in their joy. In this way, in contrast to the actors on the theater stage, the idea of the early research of the cinematographic art of the appearance of the participation effect by connecting the characters to their experiences as their own gaze is reflected in the feature film.